123I‐FP‐CIT SPECT [(123) I‐2β‐carbomethoxy‐3β‐(4‐iodophenyl)‐N‐(3‐fluoropropyl) nortropane single photon emission computed tomography] Imaging in a p.A53T α‐synuclein Parkinson's disease cohort versus Parkinson's disease. Issue 11 (4th October 2018) - Koros, Christos; Simitsi, Athina; Prentakis, Andreas; Beratis, Ion; Papadimitriou, Dimitra; Kontaxopoulou, Dionysia; Fragkiadaki, Stella; Papagiannakis, Nikolaos; Seibyl, John; Marek, Kenneth; Papageorgiou, Sokratis G.; Trapali, Xenia Geronicola; et al.
ABSTRACT: Background: The p.A53T point mutation in the α‐synuclein gene ( SNCA ) is a rare but highly relevant cause of autosomal dominant Parkinson's disease (PD). Objectives: The objective of this study was to assess striatal dopaminergic denervation in a cohort of symptomatic carriers of the p.A53T SNCA mutation as compared to PD patients. Methods: Data from the Parkinson's Progression Markers Initiative database of 11 symptomatic p.A53T SNCA mutation carriers who underwent 123I‐FP‐CIT SPECT [(123) I‐2β‐carbomethoxy‐3β‐(4‐iodophenyl)‐N‐(3‐fluoropropyl) nortropane single photon emission computed tomography] imaging at our site were compared with those of 33 age‐, sex‐, and disease duration–matched PD patients. Results: The p.A53T mutation carriers had significantly lower caudate nucleus binding ratio both contralaterally and ipsilaterally to the most affected side ( P = .002 and P = .006) and a decreased contralateral caudate/putamen signal ratio ( P = .007) as compared to PD. A similar degree of striatal asymmetry was observed in both subgroups. No correlation between scores in neuropsychological tests and caudate nucleus dopaminergic denervation could be demonstrated. Conclusions: PD patients harboring the p.A53T SNCA mutation show evidence of a more severe nigrostriatal denervation, especially evident in the caudate nucleus. The lack of significant differences in the putaminal binding ratios may reflect a floor effect or a true preferential targeting of the caudate terminals in p.A53T SNCA ‐associated PD. © 2018 International Parkinson and Movement Disorder Society